Consent and sex in vulnerable adults: a review of case law. (28th June 2012) - Curtice, Martin; Mayo, Jonathan; Crocombe, Juli
Abstract : Accessible summary: People with learning disabilities may not know about sexual relationships. People with learning disabilities may need education about sexual relationships. People with learning disabilities may need education about contraception. Summary: The introduction of the Mental Capacity Act 2005 has brought to the fore issues regarding capacity in various clinical settings. One important area where capacity assessment is often vital is regarding vulnerable people being able to consent to sexual relations. Case law from courts has evolved with regard to this sometimes complex and emotive issue both before and after the implementation of the Mental Capacity Act 2005. This article describes and analyses the evolution of such case law which predominantly involves people with learning disabilities. In doing so, it explains key principles and tests both for consenting to sexual relations and for the use of contraception which can be applied and used in clinical practice. The article also discusses the associated human rights issues for vulnerable adults in trying to balance the right to sexual relations as part of an individual's private life whilst managing potential abuse issues.